Technique To Fabricate A Facial Moulage Using Party Face Mask - Lambat, Apurva; Madhav, V.N. V; Khadse, Shreeyash; Kamble, Atharva; Patel, Khusboo (Journal of Neonatal Surgery, 2025)
Even when the patient is not present, it is easier to comprehend how the face prosthesis is oriented and positioned in relation to other facial landmarks because to the precision of the facial moulding. When creating imprints for the purpose of creating facial mouldings, a patient's face is directly cast on dental plaster, alginate, and elastomeric impression material, each of which has drawbacks of its own. These factors led to the development of a unique clinical approach that is shown here to manufacture stock trays utilizing party masks in order to make precise impressions and support the impression material as it sets and pours